Answer:
k = 1 ,k = - 2
Step-by-step explanation:
Given that
x + y + k z = 6
x + k y + z = 3
k x + y + z = 9
If the determinate of given equation is zero then the above linear equation do not have a unique solution.
![\begin{bmatrix}1 & 1 & k\\ 1 & k & 1\\ k & 1 & 1\end{bmatrix}=0](https://img.qammunity.org/2021/formulas/engineering/college/784eqfsm3hhji1x7gif7vt5sf2vvhngpvi.png)
Lest solve the above determinate
(k - 1 ) - (1 - k) + k( 1 - k²) = 0
K - 1 - 1 + k+ k - k³ = 0
3 k - 2 - k³ = 0
k³ - 3 k + 2 = 0
(k - 1 ) ( k² + k - 2 ) = 0
( k - 1 )(k -1 )(k+2) = 0
k = 1 ,k = - 2
That is why the value of k will be 1 and - 2 .